Virtual collaborative creative engagement in a pandemic world: creative connection for older adults with lived experience of dementia - Henderson, Julia; Reid, Colleen (Frontiers in Health Services, 2023)
Introduction: Older adults were disproportionately affected by COVID-19, and isolation and loneliness became key risk factors for mental illness and decreased quality of life. Older adults with lived experience of dementia and their care partners experienced isolation, loneliness, anxiety and depression, already heightened due to social stigma. Reduced access to resources was a notable problem. Objective: This Canadian qualitative study investigates the Raising the Curtain on the Lived Experience of Dementia (RTC) Project’s virtual turn in program delivery during the pandemic, asking “How did virtual collaborative creative engagement (CCE) impact well-being for people living with dementia and their care partners?”; and “What are key elements of RTC’s unique virtual CCE approach?” Methods: The study employs reflexive thematic analysis to analyse interviews and focus groups with the project’s artist facilitators, researchers, peer collaborators living with dementia, and their care partners. Findings: Themes describe key elements of RTC’s unique approach to virtual CCE and include: “Adjusting Expectations and Adapting to Technology”; “Re-imagining Creative Engagement in Virtual Space”; “Sustaining Reciprocal Caring, Learning, and Support”; “Disrupting Stigma and Welcoming a Wider Audience”; and “Supporting Well-being through Empowerment, Community, and Creativity.” Discussion: Findings offer new perspectives on how virtual CCE not only has the potential to decrease loneliness and isolation and associated mental health risks for older adults living with dementia and their care partners, but also can work to disrupt stigmatizing representations of dementia, promote inclusion, and enhance citizenship.